2006
DOI: 10.1007/s10719-006-7922-6
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression and glycosylation of plasma proteins in rheumatoid arthritis

Abstract: Altered glycosylation of plasma proteins has been directly implicated in the pathogenesis of rheumatoid arthritis (RA). The present study investigated the changes in the Concanavalin-A (Con-A)-bound plasma proteins in the RA patients in comparison to that of the healthy controls. Two proteins (MW approximately 32 kDa and approximately 62 kDa) showed an alteration in expression while an altered monosaccharide profile (high mannose) was observed in the approximately 62 kDa protein in the samples collected from R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 21 publications
1
22
0
4
Order By: Relevance
“…Another major glycoprotein, transferrin, accounts for a small proportion of the tri-antennary oligosaccharides found in healthy adults [22], and IgG and haptoglobin reportedly exhibit bi-antennary [23,24] rather than tri-antennary oligosaccharides. However, alteration in AGP N-glycans in RA is reported to involve only fucosylation, and proteomic analysis of serum in RA using 2-D PAGE and lectins shows changes in IgG, haptoglobin, and two unknown glycoproteins, but not in AGP [8]. Thus, the observed increase in tri-antennary oligosaccharides may occur in glycoproteins other than AGP, supporting the importance of analyzing whole serum N-glycans rather than just oligosaccharides on purified glycoproteins.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Another major glycoprotein, transferrin, accounts for a small proportion of the tri-antennary oligosaccharides found in healthy adults [22], and IgG and haptoglobin reportedly exhibit bi-antennary [23,24] rather than tri-antennary oligosaccharides. However, alteration in AGP N-glycans in RA is reported to involve only fucosylation, and proteomic analysis of serum in RA using 2-D PAGE and lectins shows changes in IgG, haptoglobin, and two unknown glycoproteins, but not in AGP [8]. Thus, the observed increase in tri-antennary oligosaccharides may occur in glycoproteins other than AGP, supporting the importance of analyzing whole serum N-glycans rather than just oligosaccharides on purified glycoproteins.…”
Section: Discussionmentioning
confidence: 93%
“…One particularly dramatic oligosaccharide change associated with disease is reduced galactose in IgG N-glycans seen in patients with rheumatoid arthritis (RA) [1]. Fucosylation of IgG [2] and N-glycan microheterogeneities in α1-acid glycoproteins (AGP) [3,4], transferrin [5], haptoglobin [6], α2-macrogloblin [7], and other plasma proteins [8] have also been reported in RA, although it is not known how alterations are associated with symptoms [9]. Several methods have been applied to the analysis of IgG N-glycans, such as reversed phase-high performance liquid chromatography (RP-HPLC), liquid chromatography-mass spectrometry (LC-MS), lectin analysis, and high pH anion exchange chromatography-pulsed amperometric detection (HPAEC-PAD) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Then CRP replaced ESR in the next developed models for predicting disease activity since it was a more reliable acute phase reactant and sensitive to short-term changes in clinical activity than ESR [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that, in the etiology of RA, alterations in the glycosylation of plasma proteins are involved [4,10], including transferrin which consists of a polypeptide sequence of two oligosaccharide chains being N-glycosidally bound [2]. The association between CDT and RA was found by Sillanaukee et al [13].…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a disease in which the glycosylation of plasma proteins is altered [4,10]. Evidence for these abnormalities was the presence of IgG isoforms having different numbers of galactose residues [11,15], due to reduced galactosyltransferase activity in lymphocyte B [9].…”
mentioning
confidence: 99%